The role of age and oral lexical competence in false belief understanding by children and adolescents with hearing loss. - González-Cuenca, Antonia Mercedes; Quintana-García, Inmaculada; Barajas-Esteban, María Carmen; Linero-Zamorano, María José (Alexander Graham Bell Association for the Deaf and Hard of Hearing, 2007)
In the past decade, most studies have reported that children who are deaf and hard of hearing who have parents with typical hearing experience a serious delay in the understanding of false belief. False belief understanding consists of the ability to infer that someone else believes that something is true when one knows it to be wrong. This ability has been considered a reference point in studying the development of theory of mind (ToM). The main aim of this work is to evaluate the relationship between age, oral language and understanding of false belief in subjects who are deaf and hard of hearing. We investigated the relationship between age and ToM when the maximum age of participants included in the study was increased to 19 years. We also studied the relationship between the oral linguistic level of the participants and their performance in ToM. The sample consisted of 54 participants who are deaf and hard of hearing (ages 6 to 19 years) and who come from families with typical hearing. The results show that only from age 14 years onward is there a high percentage of success in the resolution of false belief tasks. Besides age, the level of oral lexical competence is a variable that can help to explain the differences in ToM performance among individuals with hearing loss.
https://directory.agbell.org/Advocacy/Volta-Review " The journal is published once annually as an open access publication, with each issue being available in the fall. "
Keywords: Sordera en niños; Sordos - Psicología; Deafness; Children; Adolescents; False belief